Branched convolutional neural networks incorporated with Jacobian deep regression for facial landmark detection. (October 2019) - Zhu, Meilu; Shi, Daming; Gao, Junbin
Abstract: Facial landmark detection is to localize multiple facial key-points for a given facial image. While many methods have achieved remarkable performance in recent years, the accuracy remains unsatisfactory due to some uncontrolled conditions such as occlusion, head pose variations and illumination, under which, the L2 loss function is conventionally dominated by errors from those facial components on which the landmarks are hard predicted. In this paper, a novel branched convolutional neural network incorporated with Jacobian deep regression framework, hereafter referred to as BCNN-JDR, is proposed to solve the facial landmark detection problem. Our proposed framework consists of two parts: initialization stage and cascaded refinement stages. We firstly exploit branched convolutional neural networks as the robust initializer to estimate initial shape, which is incorporated with the knowledge of component-aware branches. By virtue of the component-aware branches mechanism, BCNN can effectively alleviate this issue of the imbalance errors among facial components and provide the robust initial face shape. Following the BCNN, a sequence of refinement stages are cascaded to fine-tune the initial shape within a narrow range. In each refinement stage, the local texture information is adopted to fit the facial local nonlinear variation. Moreover, our entire framework is jointly optimized via the Jacobian deep regression optimization strategy in an end-to-end manner. Jacobian deep regression optimization strategy has an ability to backward propagate the training error of the last stage to all previous stages, which implements a global optimization approach to our proposed framework. Experimental results on benchmark datasets demonstrate that the proposed BCNN-JDR is robust against uncontrolled conditions and outperforms the state-of-the-art approaches.